Summary Lecture as a Delay Organizer of Cultural Content Knowledge: The Case of Classical Mechanics - Galili, Igal; Goren, Ehud (Science & education, 2023)
Regular disciplinary instruction of introductory physics at high school often misses a holistic perspective of the subject matter, its structure, and hierarchy. We have considered the domain of classical mechanics as taught at school and provided such a perspective in the form of a summative lecture which frames content in the triadic structure (nucleus-body-periphery)—discipline-culture. To facilitate this approach, we have reviewed the history of mechanics, revealed its origin in the fusion of the theory of motion in natural philosophy with the theory of work devices—mechanics. We discussed a summary lecture after an introductory course in mechanics. We argued for this teaching which promotes cultural content knowledge of classical mechanics stimulates learning about essential aspects of nature of science and scientific knowledge. Furthermore, we report on the experimental lecture which presented mechanics structured as a discipline-culture. The nucleus of mechanics, Newton’s laws of motion, contrasted by conceptual alternatives, emphasized mechanics as a fundamental theory of physics. The students and preservice teachers of our sample reacted positively to the new perspective, expressed engagement and interest. The assessment revealed the beneficial impact of the discipline-culture paradigm even if applied as a short conceptual summary. Beyond the new perspective and affective impact, the lecture served as a delay organizer of students’ knowledge, upgrading it to the cultural content knowledge. Besides knowledge improvement, we were evident to students’ curiosity, both ontological and epistemic.